ESCAPING OF LACKNESS TROUGH FICTION FOR DESIRE AND EMPTINESS FULFILMENT - Arianto, Tomi; Ambalegin, Ambalegin (IdeBahasa, 2020)
Popular fiction is a work that can not be released from the audience and special formulas so that it can be a place of escape from all human fatigue in all forms of activity. This research aimed to find the phenomenon of escaping lackness trough popular fiction. By using a popular fiction approach Cawelty (1976) and Adi (2011) combined with the concept of psychoanalysis, the researchers tried to explore the passion and emptiness in popular iron man 3 movie through characters, settings, and plots in the story. By using the audience analysis approach in descriptive qualitative method, there were several factors that form the formula in this action iron man 3 story to fill the audience's dreams and fill the emptiness in the audience so that the achievement of popularity can be achieved. The results of this study showed that Stark as the protagonist was described as a special genius who could develop knowledge and technology to respond to natural phenomena that had not yet occurred. The ability of producer to create images of the desires of technology power with the needs of the community made this film successfully debuted. Spiced up with the story of romanticism Stark and his lover add to the surprises that were generated in accordance with the desire that involves the audience immersed in the story.